Overexpression of plastidial thioredoxins f and m differentially alters photosynthetic activity and response to oxidative stress in tobacco plants - REY, Pascal; SANZ-BARRIO, Ruth; INNOCENTI, Gilles; KSAS, Brigitte; COURTEILLE, Agathe; RUMEAU, Dominque; ISSAKIDIS-BOURGUET, Emmanuelle; FARRAN, Immaculada (Frontiers in Plant Science, 2013)
Plants display a remarkable diversity of thioredoxins (Trxs), reductases controlling the thiol redox status of proteins. The physiological function of many of them remains elusive, particularly for plastidial Trxs f and m, which are presumed based on biochemical data to regulate photosynthetic reactions and carbon metabolism. Recent reports revealed that Trxs f and m participate in vivo in the control of starch metabolism and cyclic photosynthetic electron transfer around photosystem I, respectively. To further delineate their in planta function, we compared the photosynthetic characteristics, the level and/or activity of various Trx targets and the responses to oxidative stress in transplastomic tobacco plants overexpressing either Trx f or Trx m. We found that plants overexpressing Trx m specifically exhibit altered growth, reduced chlorophyll content, impaired photosynthetic linear electron transfer and decreased pools of glutathione and ascorbate. In both transplastomic lines, activities of two enzymes involved in carbon metabolism, NADP-malate dehydrogenase and NADP-glyceraldehyde-3-phosphate dehydrogenase are markedly and similarly altered. In contrast, plants overexpressing Trx m specifically display increased capacity for methionine sulfoxide reductases, enzymes repairing damaged proteins by regenerating methionine from oxidized methionine. Finally, we also observed that transplastomic plants exhibit distinct responses when exposed to oxidative stress conditions generated by methyl viologen or exposure to high light combined with low temperature, the plants overexpressing Trx m being notably more tolerant than Wt and those overexpressing Trx f. Altogether, these data indicate that Trxs f and m fulfill distinct physiological functions. They prompt us to propose that the m type is involved in key processes linking photosynthetic activity, redox homeostasis and antioxidant mechanisms in the chloroplast.